FITOMASSAS DE BABY COUVE CULTIVADAS EM MIX E POSIÇÃO DE MATERIAL REFLETOR COLORIDO NA BANCADA DE CULTIVO - Dias Santana , Tamiris; Costa , Edilson; Freitas Souza , Iasmin; Pacheco de Almeida Prado Bortolheiro , Fernanda; ferreira da Silva Binotti , Flávio; Pradi Vendruscolo, Eduardo (ANAIS DO ENIC, 2026)
-